Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To find the Laurent series expansion of [tex]\( f(z) = \frac{1}{z^2 + 2z} \)[/tex] for [tex]\( 1 < |z - 1| < 3 \)[/tex], we start with partial fraction decomposition.
First, we can rewrite [tex]\( f(z) \)[/tex] as:
[tex]\[ f(z) = \frac{1}{z^2 + 2z} = \frac{1}{z(z + 2)}. \][/tex]
To decompose [tex]\( \frac{1}{z(z + 2)} \)[/tex] into partial fractions, we write:
[tex]\[ \frac{1}{z(z + 2)} = \frac{A}{z} + \frac{B}{z + 2}. \][/tex]
Solving for [tex]\( A \)[/tex] and [tex]\( B \)[/tex]:
[tex]\[ 1 = A(z + 2) + Bz. \][/tex]
Setting [tex]\( z = 0 \)[/tex]:
[tex]\[ 1 = A(2), \][/tex]
[tex]\[ A = \frac{1}{2}. \][/tex]
Setting [tex]\( z = -2 \)[/tex]:
[tex]\[ 1 = B(-2), \][/tex]
[tex]\[ B = -\frac{1}{2}. \][/tex]
So, the partial fractions decomposition is:
[tex]\[ \frac{1}{z(z + 2)} = \frac{1}{2z} - \frac{1}{2(z + 2)}. \][/tex]
We now need to express this in a form suitable for the Laurent series in the given annulus [tex]\( 1 < |z - 1| < 3 \)[/tex].
The expression [tex]\( \frac{1}{2z} \)[/tex] is already in a suitable form.
For [tex]\( \frac{1}{2(z + 2)} \)[/tex], we note that [tex]\( z + 2 = (z - 1) + 3 \)[/tex].
We will write this expression in terms of [tex]\( \frac{1}{z-1} \)[/tex]:
[tex]\[ \frac{1}{z + 2} = \frac{1}{(z - 1) + 3}. \][/tex]
Using the series expansion for [tex]\( \frac{1}{a+b} \)[/tex], where [tex]\( |b| < |a| \)[/tex],
[tex]\[ \frac{1}{a+b} = \frac{1}{a} \cdot \frac{1}{1 - \left(-\frac{b}{a}\right)} = \frac{1}{a} \sum_{n=0}^\infty \left(-\frac{b}{a}\right)^n. \][/tex]
Here [tex]\( a = 3 \)[/tex] and [tex]\( b = z-1 \)[/tex], so:
[tex]\[ \frac{1}{(z - 1) + 3} = \frac{1}{3} \cdot \frac{1}{1 - \left(-\frac{z-1}{3}\right)} = \frac{1}{3} \sum_{n=0}^\infty \left( \frac{z-1}{3} \right)^n. \][/tex]
Therefore,
[tex]\[ \frac{1}{z + 2} = \frac{1}{3} \sum_{n=0}^\infty \left( \frac{z-1}{3} \right)^n = \sum_{n=0}^\infty \frac{(z-1)^n}{3^{n+1}}. \][/tex]
Now multiply by [tex]\(-\frac{1}{2}\)[/tex]:
[tex]\[ -\frac{1}{2(z + 2)} = -\frac{1}{2} \sum_{n=0}^\infty \frac{(z-1)^n}{3^{n+1}} = - \sum_{n=0}^\infty \frac{(z-1)^n}{2 \cdot 3^{n+1}} = - \sum_{n=0}^\infty \frac{(z-1)^n}{2^{(n+1)} \cdot 3}. \][/tex]
Thus, our Laurent Series in the given annulus is:
[tex]\[ \frac{1}{2z} - \sum_{n=0}^\infty \frac{(z-1)^n}{2 \cdot 3^{n+1}}. \][/tex]
It can be written as:
[tex]\[ f(z) = \frac{1}{2z} - \sum_{n=0}^\infty \frac{(z-1)^n}{6 \cdot 3^n}. \][/tex]
This is the required Laurent series expansion for the given function in the specified region.
First, we can rewrite [tex]\( f(z) \)[/tex] as:
[tex]\[ f(z) = \frac{1}{z^2 + 2z} = \frac{1}{z(z + 2)}. \][/tex]
To decompose [tex]\( \frac{1}{z(z + 2)} \)[/tex] into partial fractions, we write:
[tex]\[ \frac{1}{z(z + 2)} = \frac{A}{z} + \frac{B}{z + 2}. \][/tex]
Solving for [tex]\( A \)[/tex] and [tex]\( B \)[/tex]:
[tex]\[ 1 = A(z + 2) + Bz. \][/tex]
Setting [tex]\( z = 0 \)[/tex]:
[tex]\[ 1 = A(2), \][/tex]
[tex]\[ A = \frac{1}{2}. \][/tex]
Setting [tex]\( z = -2 \)[/tex]:
[tex]\[ 1 = B(-2), \][/tex]
[tex]\[ B = -\frac{1}{2}. \][/tex]
So, the partial fractions decomposition is:
[tex]\[ \frac{1}{z(z + 2)} = \frac{1}{2z} - \frac{1}{2(z + 2)}. \][/tex]
We now need to express this in a form suitable for the Laurent series in the given annulus [tex]\( 1 < |z - 1| < 3 \)[/tex].
The expression [tex]\( \frac{1}{2z} \)[/tex] is already in a suitable form.
For [tex]\( \frac{1}{2(z + 2)} \)[/tex], we note that [tex]\( z + 2 = (z - 1) + 3 \)[/tex].
We will write this expression in terms of [tex]\( \frac{1}{z-1} \)[/tex]:
[tex]\[ \frac{1}{z + 2} = \frac{1}{(z - 1) + 3}. \][/tex]
Using the series expansion for [tex]\( \frac{1}{a+b} \)[/tex], where [tex]\( |b| < |a| \)[/tex],
[tex]\[ \frac{1}{a+b} = \frac{1}{a} \cdot \frac{1}{1 - \left(-\frac{b}{a}\right)} = \frac{1}{a} \sum_{n=0}^\infty \left(-\frac{b}{a}\right)^n. \][/tex]
Here [tex]\( a = 3 \)[/tex] and [tex]\( b = z-1 \)[/tex], so:
[tex]\[ \frac{1}{(z - 1) + 3} = \frac{1}{3} \cdot \frac{1}{1 - \left(-\frac{z-1}{3}\right)} = \frac{1}{3} \sum_{n=0}^\infty \left( \frac{z-1}{3} \right)^n. \][/tex]
Therefore,
[tex]\[ \frac{1}{z + 2} = \frac{1}{3} \sum_{n=0}^\infty \left( \frac{z-1}{3} \right)^n = \sum_{n=0}^\infty \frac{(z-1)^n}{3^{n+1}}. \][/tex]
Now multiply by [tex]\(-\frac{1}{2}\)[/tex]:
[tex]\[ -\frac{1}{2(z + 2)} = -\frac{1}{2} \sum_{n=0}^\infty \frac{(z-1)^n}{3^{n+1}} = - \sum_{n=0}^\infty \frac{(z-1)^n}{2 \cdot 3^{n+1}} = - \sum_{n=0}^\infty \frac{(z-1)^n}{2^{(n+1)} \cdot 3}. \][/tex]
Thus, our Laurent Series in the given annulus is:
[tex]\[ \frac{1}{2z} - \sum_{n=0}^\infty \frac{(z-1)^n}{2 \cdot 3^{n+1}}. \][/tex]
It can be written as:
[tex]\[ f(z) = \frac{1}{2z} - \sum_{n=0}^\infty \frac{(z-1)^n}{6 \cdot 3^n}. \][/tex]
This is the required Laurent series expansion for the given function in the specified region.
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.